NEW CONSTITUTION - DEVELOPMENT COMMITTEE - Alimov Bakhtiyar Murodovich (Web of Journals Publishing, 2023)
The article reveals the essence of the new constitution based on the analysis of the Constitution adopted in the new edition adopted by Universal vote in the referendum of the Republic of Uzbekistan and the need for its adoption, as well as the main changes made. In contrast, the democratic changes taking place in the Republic reflect the changes made to the Constitution earlier.
Keywords: Constitution, referendum, strategy, Supreme Assembly, Judiciary, legal state.